Perception of Artisanal Mining: La Paz, Amazonia of Ecuador (Revista LIDER, 2020)
The behavior and conduct of human beings with their environment depends on multiple social, environmental and cultural variables (Touguinha & Pato, 2011). In this research, the K-Medias method was used to identify four conglomerates with low, medium and high environmental perception of the interviewees in relation to the artisanal mining activity in the parish of La Paz in the Amazonian province of Zamora Chinchipe. This study revealed a high level of awareness among La Paz residents about the environmental damage caused by artisanal mining and the negative effects on their health (personal and family). However, this does not limit their decision to continue this illegal practice when it is necessary for their economy.